Estimation of morphometric parameters of lakes based on satellite imagery data: Implications of relationships between lakes in the arid region of western Mongolia, Central Asia - Enkhbold, Altanbold; Vandansambuu, Battsengel; Yadamsuren, Gansukh; Dorjsuren, Batsuren; Dorligjav, Sandelger; Gonchigjav, Yumchmaa; Dingjun, Li; Narantsetseg, Chantsal; Ganbold, Byambadayar; Sumiya, Erdenesukh (Quaestiones Geographicae, 2025)
The relationship between reservoirs and naturally formed lakes in Mongolia has not been previously studied. This research explores potential future environmental impacts, both positive and negative, in western Mongolia. The study employs morphological analysis (MA), normalised difference water index (NDWI), volume analysis and statistical analysis of water. In the case of Airag Lake and an artificially created lake, temporal changes in lake surface area and volume exhibit inverse trends. The correlation between changes in lake area over time is highly negative (R = −0.96, p < 0.01 for the surface area), which is attributed to a decrease in Airag Lake’s area and volume during the lake water accumulation period from 2007 to 2011 and countered by an increase in Gegeen Lake’s area and volume. Conversely, the surface area of Khyargas Lake shows a strong positive correlation (R = 0.94, p < 0.0001) with Airag Lake’s area and a strong negative correlation (R = −0.88, p < 0.0001) with Gegeen Lake’s area during the period from 2007 to 2021. Based on satellite data, our findings suggest a negative relationship between changes in lake surface area and volume, indicating recent significant human impacts on lake water balance. This research explores the implications of hydropower dams and reservoirs in the region, as well as environmental concerns within the context of power production.